Schwannoma of the right colon: case report - Tenazoa Villalobos, José Richard (2024)
Colon schwannoma is an extremely rare entity that may debut as a subepithelial lesion with ulceration signs, such as melena and anemia. Imaging studies guide us to localization, while a colonoscopy biopsy is not helpful. Many times, the diagnosis and treatment are made with lesion resection, and the final diagnosis is postoperatively made with histopathology and immunohistochemistry, which shows intense positivity for S100 and vimentin in tumor cells with a KI67 proliferation index of less than 1%, therefore, it is concluded that this is a benign lesion. We present this case due to its pre- and intraoperative diagnostic difficulty, non-specific symptoms, and its definitive diagnosis that was achieved with immunohistochemistry.